To Study the GenZ Perception About Netflix Subscription Plan in Ahmedabad City - Indraraj Roy; Krudit Mori; Jignesh Vidani (International Journal of Educational and Life Sciences, 2024)
This research examines the perceptions of Generation Z in Ahmedabad on Netflix subscription plans, particularly on key factors that guide their decisions on subscribing to the platform. The research utilizes hypothesis testing to evaluate variables such as affordability, localized content, promotional offers, peer influence, and user experience. Findings show that students and young professionals are highly associated with affordability as a key consideration. The study also highlights the prominence of localized content, which postulates that culturally relevant programs increase the appeal of viewing on Netflix in regional markets. Promotion and peer influence are also influences, highlighting social validation in addition to the use of targeted discounts as a motivational factor for subscriptions. Despite weak associations with factors such as binge-watching and user-friendly interface, research shows that an overall approach to include affordability, cultural relevance, and positive user experiences is what would attract and retain Generation Z subscribers. Implications would then spread to marketing strategies and content development targeting improvement in engagement with the group. Future studies should be extended to comparative studies with other OTT platforms, broader demographic insights, and the impact of economic and technological shifts on consumer behavior. These findings contribute to a deeper understanding of digital consumption patterns and strategic approaches in the OTT industry.